Technology in the work of Jack Kerouac and William S. Burroughs - Nash, Catherine (2008)
This thesis explores the use and significance of technologies of representation in the work of Jack Kerouac (1922-1969) and William S. Burroughs (1914-1997), particularly in relation to the development of ideas of free and improvisatory expression in the 1950s. More specifically it focuses on the role played by the technologies of the typewriter and tape recorder in the textual production of key works of each writer and how these technologies are also thematically important in their exploration of the topics of individual creativity and freedom in relation to social and technological control. It also examines the centrality of epistolary practice in the creative process. The focus on these technologies will allow the thesis to develop from this base into a wider exploration of many of the key themes of Kerouac’s and Burroughs’ work, placing them within a context of wider debates and concerns over the power of mass media and technology among contemporary social commentators as well as writers of the Beat generation.